Intentional rounding: a staff led quality improvement intervention in the prevention of patient falls - Morgan, L; Flynn, L; Robertson, E; New, S; McCulloch, P; Forde-Johnstone, C (John Wiley and Sons Ltd, 2016)
Aims and objectives: This study designed and evaluated the use of a specific implementation strategy to deliver a nursing staff led Intentional Rounding intervention to reduce inpatient falls. Background: Patient falls are a common cause of harm during hospital treatment. Intentional Rounding has been proposed as a potential strategy for prevention, but has not received much objective evaluation. Previous work has suggested that logical interventions to improve patient care require an integrated implementation strategy, utilising teamwork training and systems improvement training, to instigate positive change and improvement. Methods: Customised Intentional Rounding was implemented and evaluated as part of a staff led quality improvement intervention to reduce falls on a neuroscience ward. Intentional Rounding was instigated using a pre-specified implementation strategy, which comprised of; (a) engagement and communication activities, (b) teamwork and systems improvement training, (c) support and coaching, and (d) iterative Plan-Do-Check-Act cycles. Process (compliance with hourly visiting to patients by staff) and outcome (incidence of falls) measures were recorded pre- and post-intervention. Falls measured on the active ward were compared with incidence of falls in 50 wards across the rest of the same Trust. Results: There was a 50% reduction in patient falls on the active ward, versus a minimal increase across the rest of the Trust (3.48%). Customised Intentional Rounding, designed by staff specifically for the context, appeared to be effective in reducing patient falls. Conclusions: Improvement programmes based on integrating teamwork training and staff-led systems redesign together with a pre-planned implementation strategy, can deliver effective change and improvement. Relevance to clinical practice: This study demonstrates, through the implementation of a specific strategy, an effective improvement intervention to reduce patient falls. It provides insight into the effective design and practical implementation of integrated improvement programmes to reduce risk to patients at the frontline.